2013
DOI: 10.2527/jas.2012-6029
|View full text |Cite
|
Sign up to set email alerts
|

Does β-hydroxybutyrate concentration influence conception date in young postpartum range beef cows?1

Abstract: Cows in negative energy balance after calving often have reduced reproductive performance, which is mediated by metabolic signals. The objective of these studies was to determine the association of serum metabolites, days to first postpartum ovulation, milk production, cow BW change, BCS, and calf performance with conception date in spring-calving 2- and 3-yr-old beef cows grazing native range. In Exp. 1, cows were classified by conception date in a 60-d breeding season as early (EARLY; conceived in first 15 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 23 publications
1
28
6
Order By: Relevance
“…However, serum concentrations of NEFA did not differ between treatments (Table 7). Similar results were reported by Mulliniks et al (2013), in their work with beef cows grazing on native ranges during post-calving.…”
Section: Discussionsupporting
confidence: 78%
“…However, serum concentrations of NEFA did not differ between treatments (Table 7). Similar results were reported by Mulliniks et al (2013), in their work with beef cows grazing on native ranges during post-calving.…”
Section: Discussionsupporting
confidence: 78%
“…Nevertheless, βHB levels had not influence days from calving to conception, unlike Mulliniks et al [2] who found that low βHB concentrations were associated with an earlier conception date in beef cows. The contrasting experimental results may be explained by the fact that the βHB values that impaired reproduction cited by the above authors were higher at − 30-d (0.71 mmol/L) than those of our experiment (0.48 mmol/L).…”
Section: Discussioncontrasting
confidence: 62%
“…Data in the literature reveal that restricting pregnant cows' intake during the late gestation period results in weight loss, BCS loss and high serum concentrations of NEFA and βHB, which lead to long periods of negative energy balance in both dairy [27,28] and beef cows [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particular attention must be reserved to the meaning of an increased plasma BHB in the antepartum period. Ospina et al [12], and more recently Mulliniks et al [23], reported how antepartum plasma BHB may represent a signal of increased risk of pathologies at the beginning of lactation, both for dairy and beef cattle. In our case, the low yield of BWT-C cows in the first month of lactation was not associated to increased pathologies, as confirmed by a "normal" metabolic profile ( Table 5).…”
Section: Discussionmentioning
confidence: 97%